PROSEDUR TERAPI RADIASI EKSTERNA PADA PASIEN KANKER KANDUNG KEMIH DENGAN METASTASIS ARTICULATIO COXAE - Dwi Sugeng Supriyadi; Dria Wanadi; Himawan Setyono (JRI (Jurnal Radiografer Indonesia), 2021)
ABSTRACT Background: It has been conducted research about external radiation therapy technique of bladder cancer with articulatio coxae metastasis at Dr. Moewardi Hospital Surakarta in order to explain the procedure of external radiation therapy in bladder cancer with articulatio coxae metastasis and the purpose of asymmetric radiation field that used in external radiation therapy of bladder cancer with articulatio coxae metastasis. Methods: The type of research conducts is an observational research with case report approach conducted by using direct observation method, interview with radiation oncologist and radiation technologies as well as documenting the data about external radiation therapy of bladder cancer with articulatio coxae metastasis. Results: From the research result, it is obtained the data that external radiation therapy technique of bladder cancer patient with articulatio coxae metastasis is used asymmetric whole pelvic field where right border more wide than left border. The purpose of using asymmetric field is to reach articulatio coxae metastasis in radiation field, to decrease skin dose and time efficiency of radiation therapy. Conclusions: From a technical point of view, for time efficiency by considering many patients, there is only one plane therapy and the plane can be carried out in an asymmetrical field between the right and left. While the goal from a clinical perspective is to reach the articulatio coxae into the radiation field and reduce the dose received by the skin.